Library
▹
Essentials
▹
Functions
Proposition 1.5.12.
Let
W
,
X
,
Y
,
Z
be sets,
f
:
W
→
X
,
g
:
X
→
Y
,
h
:
Y
→
Z
be
functions
. Then:
(
h
∘
g
) ∘
f
=
h
∘ (
g
∘
f
)
Proof.
Let
w
∈
W
. Then
(
h
∘
g
)(
f
(
w
))
=
h
(
g
(
f
(
w
)))
=
h
((
g
∘
f
)(
w
))
.
References.
https://en.wikipedia.org/wiki/Function_composition#Properties
https://mathworld.wolfram.com/Composition.html
https://proofwiki.org/wiki/Composition_of_Mappings_is_Associative
https://coq.inria.fr/library/Coq.Program.Combinators.html#compose_assoc
https://leanprover-community.github.io/mathlib_docs/init/function.html#function.comp.assoc